Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1038/sj.jp.7200408
|View full text |Cite
|
Sign up to set email alerts
|

Placental Transfusion: Umbilical Cord Clamping and Preterm Infants

Abstract: OBJECTIVE:To investigate the clinical effects of early versus late cord clamping in preterm infants. STUDY DESIGN:A total of 32 premature infants were prospectively randomized. The following parameters were measured: Initial spun hematocrit (Hct), hemoglobin (Hgb), red blood cell (RBC) counts, frequency of blood transfusions, peak serum bilirubin, mean blood pressure (MBP), oxygen index, intraventricular hemorrhage, and significant patent ductus arteriosus (PDA). RESULTS:Over the 4-week study period, the delay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
67
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 14 publications
2
67
0
3
Order By: Relevance
“…Most of the placental transfusion takes place in the first 3 min after birth; 50 to 70% of the volume transfuses in the first minute. 1 Previous studies regarding the delayed cord clamping have had mixed results. Several did not show a significant difference in hematocrit of neonates between the ECC and LCC groups, 2,9 whereas others demonstrated a marked rise hematocrit during the first hours of neonatal life in the LCC group.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Most of the placental transfusion takes place in the first 3 min after birth; 50 to 70% of the volume transfuses in the first minute. 1 Previous studies regarding the delayed cord clamping have had mixed results. Several did not show a significant difference in hematocrit of neonates between the ECC and LCC groups, 2,9 whereas others demonstrated a marked rise hematocrit during the first hours of neonatal life in the LCC group.…”
Section: Introductionmentioning
confidence: 98%
“…No prior studies have reported findings about polycythemia in these neonates. 1,10 The question of early versus late umbilical cord clamping is still unanswered. This study was designed to compare the effect of early and late umbilical cord clamping on neonatal hematocrit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most of the studies in the literature have found higher haemoglobin and haematocrit levels in delayed clamping groups, some studies have reported no difference [7,8].…”
Section: Introductionmentioning
confidence: 94%
“…Many studies have shown that delayed cord clamping leads to remarkable decreases in risks of morbidity such as intraventricular haemorrhage and necrotising enterocolitis in preterm infants. Delayed cord clamping provides an additional 20 to 30 ml of blood from the placenta to the infant and this additional blood volume is linked with neonatal benefits including better systemic pressure, a reduced need for inotropic support and fewer blood transfusions [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%